2015
DOI: 10.12790/jkssh.2015.20.3.96
|View full text |Cite
|
Sign up to set email alerts
|

Volar Locking Plate Fixation for Distal Radius Fractures in Hemodialysis Patients

Abstract: Purpose: Although the possibility of distal radius fractures is strong in hemodialysis patients, there are many difficult problems such as the bleeding tendency, hypervascularity and injury to arteriovenous fistula. We studied the outcomes of open reduction and volar locking plate fixation of the distal radius fractures in hemodyalisis patients with ipsilateral arteriovenous fistula. Methods:From 2007 to 2009, a retrospective chart review was performed of eleven hemodialysis patients who underwent volar lockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The authors 51) suggested that meticulous hemostasis without a tourniquet may be appropriate in patients with an ipsilateral AVF. On the other hand, Im et al 52) reported on treating 11 cases of DRF with volar plating, in which tourniquets were used during all surgeries; however, no complications such as hematoma or fistula occlusion were observed. Additionally, Hyatt et al 53) suggested that dorsal bridge plate fixation may be the optimal treatment for patients with an ipsilateral AVF, multiple comorbidities, osteoporotic bone, and a need for immediate weight-bearing.…”
Section: Perioperative Managementmentioning
confidence: 99%
“…The authors 51) suggested that meticulous hemostasis without a tourniquet may be appropriate in patients with an ipsilateral AVF. On the other hand, Im et al 52) reported on treating 11 cases of DRF with volar plating, in which tourniquets were used during all surgeries; however, no complications such as hematoma or fistula occlusion were observed. Additionally, Hyatt et al 53) suggested that dorsal bridge plate fixation may be the optimal treatment for patients with an ipsilateral AVF, multiple comorbidities, osteoporotic bone, and a need for immediate weight-bearing.…”
Section: Perioperative Managementmentioning
confidence: 99%